Regulations affecting international banking operations of bank and non-banks in Belgium-Luxembourg, France, Germany, the Netherlands, Sweden, Switzerland, the United Kingdom - Organisation for Economic Co-operation and Development (Paris : Organisation for Economic Co-operation and Development, 1981)
Euromarkets and other international operations of banks and non-banks of an individual country may be affected by various kinds of regulations applying in that country, notably by exchange control, minimum reserve requirements, prudential regulations, interest rate controls and tax regulations. This volume contains a systematic and comprehensive survey of such regulatory frameworks in seven countries.
"1981-1."
osc 6/10/17
Loans
Keywords: Banking law; Banks and banking, International; Euro-dollar market